36*6(2+2+2)=

Simple and best practice solution for 36*6(2+2+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36*6(2+2+2)= equation:


Simplifying
36 * 6(2 + 2 + 2) = 0

Combine like terms: 2 + 2 = 4
36 * 6(4 + 2) = 0

Combine like terms: 4 + 2 = 6
36 * 6(6) = 0

Multiply 36 * 6
216 * 6 = 0

Multiply 216 * 6
1296 = 0

Solving
1296 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 850=x-(x*0.3) | | -22=8+6x | | 850=x-(x*0.2) | | 850=x-(x*0.25) | | 5a+4d=44 | | 1.08g-5=0.94 | | 5x+4x-7=47 | | -2f+6=a-(3f-2) | | 20x-60=20x+80 | | (X)+(x-3)+(3x)+(3x+4)=89 | | 3+x(3+x)=73 | | 0.1=250 | | 2800=x-(x*0.2) | | 2800=x-(x*0.25) | | 1500=x-(x*0.2) | | 2000=x-(x*0.2) | | 4500=x-(x*0.2) | | 2y+2x-5=1 | | 2x+2y-5=1 | | 2200=x-(x*0.2) | | 800=x-(x*0.2) | | 1=-(2)+3 | | x^2-(2k+3)x+3k=0 | | 6000=x-(x*0.25) | | 6000=x-(x*0.3) | | 2=-(1)+3 | | 20+4K=-7K-1 | | 103.588=10x+2y | | 2=-(1+3) | | 3500=x-(x*0.2) | | 2+3(1)=5 | | 6x+3y=5y |

Equations solver categories